Ten Commandments of Off-Pump Coronary Artery Bypass Surgery - Raja, Shahzad G. (Annals of thoracic surgery short reports, 2025)
Off-pump coronary artery bypass (OPCAB) surgery offers distinct advantages over conventional on-pump techniques, including reduced inflammatory response, lower stroke risk, and improved outcomes in high-risk patients. Despite these benefits, concerns persist regarding graft patency, incomplete revascularization, and technical complexity, limiting widespread adoption. A focused literature review was conducted using PubMed-indexed sources published between 2000 and 2025. The medical subject heading term “coronary artery bypass, off-pump” was used in combination with keywords including “hemodynamic optimization,” “conversion,” “graft patency,” and “surgical training.” Only peer reviewed randomized trials, meta-analyses, guideline-based reviews, and expert consensus articles were included. Findings were synthesized to define 10 core principles for safe and reproducible OPCAB practice. The “Ten Commandments” address key domains: patient selection, contraindication management, team readiness, stabilization techniques, hemodynamic control, complete revascularization, conversion avoidance, skill acquisition, technical refinement, and evidence-based advocacy. Each principle is supported by clinical data and practical strategies. Innovations, such as intracoronary shunting, advanced stabilizers, and artificial intelligence-guided decision-making, enhance procedural reliability and outcomes. OPCAB can be performed safely and effectively with structured preparation, multidisciplinary collaboration, and adherence to best practices. By embracing these commandments and integrating emerging technologies, surgical teams can overcome barriers to adoption, refine intraoperative techniques, and deliver individualized coronary revascularization with superior long-term outcomes.